Fetomaternal outcome of newly detected thyroid disorders among pregnant women in tertiary care hospital: a cross sectional study - Selvam, Shanmuga Sundari Panneer; Shivanna, Manjunatha; Krishnegowda, Ragupathi; Rangaswamy, Suma H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Thyroid hormones are vital for fetal development and maternal health. Both overt and subclinical thyroid disorders can lead to complications like miscarriage, preterm labor, and neonatal issues. Identifying newly detected thyroid disorders in pregnancy is crucial for improving outcomes for both mothers and babies. Methods: This cross-sectional study evaluated pregnant women newly diagnosed with thyroid disorders at a tertiary care hospital. Data on thyroid function, pregnancy complications, and neonatal health were collected and analyzed to assess the impact of these disorders. The findings aimed to enhance diagnostic methods and patient care. Results: In our study, out of 150 cases, 148 were subclinical hypothyroidism, and 2 were subclinical hyperthyroidism. Subclinical hypothyroidism in pregnancy was associated with PPH (0.7%), preeclampsia (21.3%), preterm labor (9.3%), GDM (6.7%), IUD (3.3%), neonatal death (2.7%), prematurity (12.7%), LBW (21.3%), NICU admission (28%), congenital anomalies (2%), and neonatal hypothyroidism (11.3%). These findings were consistent with other studies; however, the number of hyperthyroid cases in our study was insufficient for a thorough outcome analysis. Conclusions: Thyroid disorders during pregnancy can negatively impact both maternal and fetal outcomes, underscoring the need for routine antenatal thyroid screening.